Preparation method of blue light-emitting core-shell structure nanocrystal

Through green solvent-free mechanical grinding method, blue luminescent core-shell structure nanocrystals were prepared, which solved the problem of insufficient PLQY and stability of blue perovskite nanocrystals in the prior art, and achieved efficient photoluminescence performance and Long-term stability.

CN119144328APending Publication Date: 2024-12-17TECHN PHYSICS INST HEILONGJIANG ACADOF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292095.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high photoluminescence quantum yield (PLQY) and high stability of blue perovskite nanocrystals through green and environmentally friendly methods, especially in the blue spectrum range, and commonly used ion exchange methods are accompanied by a large number of organic solvents. use.

Method used

Using green solvent-free mechanical grinding method, CsPbBr3 nanocrystals were mixed with CsCl to form CsPbBrxCl3-x/Cs4PbBryCl6-y nanocrystals, and placed in a mixed solution of organic solvent and surfactant to stand and centrifuge to prepare Blue luminescent core-shell structure nanocrystals are produced, and the shell is introduced to supplement the halogen vacancies and passivate the non-radiative composite center on the surface of the nanocrystal.

Benefits of technology

The PLQY of the nanocrystals is significantly improved, the photoluminescence spectrum is improved, making it more suitable for penetrating the photocatalytic layer in the photomultiplier tube, and the radiation luminescence response and long-term stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144328A_ABST
    Figure CN119144328A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a blue light-emitting core-shell structure nanocrystal, and belongs to the field of radiation detection materials. The invention aims to solve the problem that high PLQY and high stability of blue luminous perovskite nanocrystals cannot be realized by using a green and environment-friendly method in the prior art. The preparation method comprises the following steps: mixing and grinding the CsPbBr3 nanocrystal and CsCl, standing in a mixed solution of an organic solvent and a surfactant, and finally centrifuging to obtain the blue light-emitting core-shell structure nanocrystal. The method is used for preparing the blue light-emitting core-shell structure nanocrystal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of radiation detection materials. Background Art

[0002] With the continuous advancement of science and technology, X-ray detection technology is increasingly widely used in fields such as materials science, medicine, and environmental monitoring. In X-ray detection, the role of photoelectric conversion materials is crucial. CsPbX3 is a new type of photoelectric conversion material, which has attracted widespread attention due to its advantages such as high photoluminescence quantum yield, high defect tolerance, and good stability. After unremitting efforts in recent years, the photoluminescence quantum yield (PLQY) of red and green perovskites is close to unity. However, the front-end photoelectrocatalytic layer of the commonly used photomultiplier tubes on the market is usually coated with alkali metal compounds (such as SbCs, etc.). These compounds have high photoelectrocatalytic efficiency for blue light and can more effectively convert light energy into electrons, thereby improving detection sensitivity. In photomultiplier tubes, blue light has a shorter wavelength and higher energy, so it can penetrate the photoelectrocatalytic layer deeper and excite more secondary electrons. However, the PLQY of blue perovskites is not satisfactory, so it is currently challenging to obtain perovskite nanocrystals with stable blue light emission.

[0003] In general, there are currently two strategies to achieve blue emission: size engineering and component engineering. Size engineering constructs quantum well structures by synthesizing 2D or quasi-2D Br-based perovskites, allowing the emission wavelength to move to the blue region based on the quantum confinement effect. However, it is inevitable that as the size decreases, the surface area to volume ratio increases rapidly, which will induce a large number of surface defects and thus reduce the PLQY. Therefore, based on this strategy, it is very challenging to achieve high PLQY in the blue spectral range. In addition, it is challenging to control the formation of a single quantum well or to achieve efficient charge transfer between different quantum wells, which usually leads to multiple emission peaks. It is worth mentioning that based on component engineering, the mixed halide perovskite CsPbBr x Cl 3-x Nanocrystals can well compensate for the above shortcomings due to their unique advantages of high blue light emission purity and easily tailorable band gap covering the entire blue light spectral range.

[0004] However, CsPbBrxCl 3-x Two major obstacles of nanocrystals have seriously inhibited the research and wider application of such materials. The large number of vacancy defects on the crystal surface and the poor crystal quality make its PLQY low and the environmental stability poor, while the existing strategy of achieving spectral regulation by ion exchange is often accompanied by the use of a large amount of organic solvents. Therefore, how to use green and environmentally friendly methods to achieve the high PLQY and high stability requirements of blue luminescent perovskite nanocrystals is a difficulty in the existing technology. Summary of the invention

[0005] The present invention aims to solve the problem that the prior art cannot use green and environmentally friendly methods to achieve high PLQY and high stability of blue-luminescent perovskite nanocrystals, and further provide a method for preparing blue-luminescent core-shell structure nanocrystals.

[0006] A method for preparing blue luminescent core-shell structure nanocrystals is carried out according to the following steps:

[0007] In an atmospheric environment, CsPbBr3 nanocrystals were mixed with CsCl and ground for 1 h to 4 h to obtain CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y nanocrystals, and then CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals are placed in a mixed solution of an organic solvent and a surfactant and allowed to stand, and finally centrifuged to obtain blue luminescent core-shell structure nanocrystals;

[0008] The CsPbBr x Cl 3-x Where x>0, and 3-x>0; the Cs4PbBr y Cl 6-y In this case, y>0 and 6-y>0.

[0009] The beneficial effects of the present invention are:

[0010] The present invention innovatively adopts a green solvent-free mechanical grinding method to prepare core-shell structured nanocrystalline CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The luminescence center of this structure is CsPbBr x Cl 3-x Nanocrystals, encapsulated in Cs4PbBr y Cl 6-y The shell layer is introduced to supplement the halogen vacancies and passivate the non-radiative recombination centers on the surface of the nanocrystals, and then placed in a mixed solution of an organic solvent and a surfactant for further passivation. The method of the present invention is not only simple in operation, but also can significantly improve the PLQY of the nanocrystals, while blue-shifting the photoluminescence spectrum of the crystals, which is more conducive to penetrating the photoelectrocatalytic layer in the photomultiplier tube and exciting more secondary electrons. Compared with CsPbBr3 nanocrystals, CsPbBr x Cl 3-x / Cs4PbBry Cl 6-y The nanocrystals exhibit enhanced radioluminescence response and long-term stability.

[0011] Instruction Manual

[0012] Figure 1 X-ray diffraction spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment;

[0013] Figure 2 The photoluminescence spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment;

[0014] Figure 3 Transmission electron microscope images of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment;

[0015] Figure 4 PLQY test graphs of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment;

[0016] Figure 5 RL spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment after X-ray excitation;

[0017] Figure 6 The photoluminescence spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment after being exposed to the atmospheric environment for different time periods. DETAILED DESCRIPTION

[0018] Specific implementation method 1: This implementation method is a method for preparing blue luminescent core-shell structure nanocrystals, which is carried out according to the following steps:

[0019] In an atmospheric environment, CsPbBr3 nanocrystals were mixed with CsCl and ground for 1 h to 4 h to obtain CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y nanocrystals, and then CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals are placed in a mixed solution of an organic solvent and a surfactant and allowed to stand, and finally centrifuged to obtain blue luminescent core-shell structure nanocrystals;

[0020] The CsPbBr x Cl 3-x Where x>0, and 3-x>0; the Cs4PbBr y Cl 6-y In this case, y>0 and 6-y>0.

[0021] The beneficial effects of this embodiment are:

[0022] This embodiment innovatively adopts a green solvent-free mechanical grinding method to prepare core-shell structured nanocrystalline CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The luminescence center of this structure is CsPbBr x Cl 3-x Nanocrystals, encapsulated in Cs4PbBr y Cl 6-y The shell layer is introduced to supplement the halogen vacancies and passivate the non-radiative recombination centers on the surface of the nanocrystals, and then placed in a mixed solution of an organic solvent and a surfactant for further passivation. This embodiment method is not only simple in technical operation, but also can significantly improve the PLQY of the nanocrystals, while blue-shifting the photoluminescence spectrum of the crystals, which is more conducive to penetrating the photoelectrocatalytic layer in the photomultiplier tube and exciting more secondary electrons. Compared with CsPbBr3 nanocrystals, CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals exhibit enhanced radioluminescence response and long-term stability.

[0023] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the organic solvent is one of toluene, cyclohexane, dimethyl sulfoxide and acetone or a mixture of several of them. Others are the same as specific embodiment 1.

[0024] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the surfactant is one or a mixture of n-octanoic acid, n-octylamine, oleic acid and oleylamine. Other aspects are the same as specific implementation method 1 or 2.

[0025] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the mass ratio of the CsPbBr3 nanocrystals to CsCl is 1:(0.2-4). Other aspects are the same as specific embodiments 1 to 3.

[0026] Specific implementation method 5: This implementation method is different from specific implementation methods 1 to 4 in that the volume ratio of the organic solvent to the surfactant in the mixed solution of the organic solvent and the surfactant is 1:(0.001-0.1). Other aspects are the same as specific implementation methods 1 to 4.

[0027] Specific embodiment 6: This embodiment is different from the specific embodiments 1 to 5 in that: the CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The mass ratio of the nanocrystals to the volume ratio of the mixed solution of the organic solvent and the surfactant is 1 mg: (0.1-10) mL. The rest is the same as the first to fifth embodiments.

[0028] Specific embodiment 7: This embodiment differs from the specific embodiments 1 to 6 in that: in the atmospheric environment, CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals are placed in a mixed solution of an organic solvent and a surfactant and allowed to stand for 1 to 200 minutes. Other aspects are the same as those of the first to sixth embodiments.

[0029] Specific implementation eight: This implementation differs from specific implementations one to seven in that the centrifugation is carried out at a rotation speed of 3000 rpm to 6000 rpm for 1 to 10 minutes. The rest is the same as specific implementations one to seven.

[0030] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that the grinding is mortar grinding or ball grinding. The rest is the same as specific embodiments 1 to 8.

[0031] Specific embodiment 10: This embodiment differs from the specific embodiments 1 to 9 in that: in an atmospheric environment, CsPbBr3 nanocrystals are mixed and ground with CsCl for 2 hours to obtain CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y nanocrystals, and then in the atmosphere, CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals were placed in a mixed solution of an organic solvent and a surfactant and allowed to stand for 10 minutes, and finally centrifuged at a speed of 6000 rpm for 10 minutes to obtain blue luminescent core-shell structure nanocrystals;

[0032] The organic solvent is toluene;

[0033] The surfactant is a mixture of n-octanoic acid and n-octylamine; the volume ratio of n-octanoic acid to n-octylamine is 1:1;

[0034] The mass ratio of the CsPbBr3 nanocrystals to CsCl is 1:0.8;

[0035] The volume ratio of the organic solvent to the surfactant in the mixed solution of the organic solvent and the surfactant is 1:0.005;

[0036] The CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The mass of the nanocrystals and the volume ratio of the mixed solution of the organic solvent and the surfactant is 1 mg:0.1 mL. The rest is the same as the first to ninth embodiments.

[0037] The following examples are used to verify the beneficial effects of the present invention:

[0038] Embodiment 1:

[0039] A method for preparing blue luminescent core-shell structure nanocrystals is carried out according to the following steps:

[0040] CsPbBr3 nanocrystals were mixed and ground with CsCl for 2 h in an atmospheric environment to obtain CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y nanocrystals, and then in the atmosphere, CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals were placed in a mixed solution of an organic solvent and a surfactant and allowed to stand for 10 minutes. Finally, they were centrifuged at 6000 rpm for 10 minutes to obtain blue luminescent core-shell nanocrystals, namely CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y ;

[0041] The CsPbBr x Cl 3-x Where x>0, and 3-x>0; the Cs4PbBr y Cl 6-y Where y>0, and 6-y>0;

[0042] The organic solvent is toluene;

[0043] The surfactant is a mixture of n-octanoic acid and n-octylamine; the volume ratio of n-octanoic acid to n-octylamine is 1:1;

[0044] The mass ratio of the CsPbBr3 nanocrystals to CsCl is 1:0.8;

[0045] The volume ratio of the organic solvent to the surfactant in the mixed solution of the organic solvent and the surfactant is 1:0.005;

[0046] The CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The ratio of the mass of the nanocrystals to the volume of the mixed solution of the organic solvent and the surfactant is 1 mg:0.1 mL.

[0047] The grinding is grinding in a mortar.

[0048] Comparative experiment:

[0049] In an atmospheric environment, the CsPbBr3 nanocrystals were placed in a mixed solution of an organic solvent and a surfactant and allowed to stand for 10 minutes, and then centrifuged at a speed of 6000 rpm for 10 minutes to obtain passivated CsPbBr3 nanocrystals, namely CsPbBr3;

[0050] The organic solvent is toluene;

[0051] The surfactant is a mixture of n-octanoic acid and n-octylamine; the volume ratio of n-octanoic acid to n-octylamine is 1:1;

[0052] The volume ratio of the organic solvent to the surfactant in the mixed solution of the organic solvent and the surfactant is 1:0.005;

[0053] The volume ratio of the mass of the CsPbBr3 nanocrystals to the mixed solution of the organic solvent and the surfactant is 1 mg:0.1 mL.

[0054] Figure 1 The X-ray diffraction spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment are shown in the figure. x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals showed Cs4PbBr at 12.76°, 25.62° and 39.6°.y Cl 6-y The characteristic diffraction peaks of nanocrystals can prove that this example successfully prepared CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y Nanocrystals.

[0055] The blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment were irradiated with 365 nm ultraviolet light to test the photoluminescence spectrum; Figure 2 The photoluminescence spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment are shown in the figure. x Cl 3-x / Cs4PbBr y Cl 6-y Compared with CsPbBr3 nanocrystals, the photoluminescence of the nanocrystals shows an obvious blue shift, from 480nm to 450nm, and the photoluminescence intensity is significantly improved.

[0056] Figure 3 The transmission electron microscope images of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment are shown in the figure. x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals have a distinct core-shell structure, and CsPbBr x Cl 3-x Nanocrystals are encapsulated in Cs4PbBr y Cl 6-y in the shell.

[0057] Figure 4 The PLQY test graphs of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment are shown in the figure. x Cl 3-x / Cs4PbBr y Cl 6-y The PLQY of the nanocrystals (63.63%) is significantly improved compared to that of CsPbBr3 nanocrystals (44.07%).

[0058] The blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment were irradiated with X-rays (tube voltage 50 kV, tube current 200 μA) to test the RL spectrum. Figure 5 Figure 1 is the RL spectrum of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment after X-ray excitation. x Cl 3-x / Cs4PbBr y Cl 6-y The X-ray photoluminescence intensity of the nanocrystals is significantly improved compared to that of CsPbBr3 nanocrystals, and the photoluminescence peak is blue-shifted from 490nm to around 460nm.

[0059] Figure 6 The photoluminescence spectra of the blue luminescent core-shell structure nanocrystals prepared in Example 1 and the passivated CsPbBr3 nanocrystals prepared in the comparative experiment after being exposed to the atmosphere for different time periods. x Cl 3-x / Cs4PbBr y Cl 6-y The environmental stability of the nanocrystals is significantly improved compared to that of CsPbBr3 nanocrystals. After 20 days in the atmosphere, the CsPbBr3 nanocrystals maintain 87% of the initial luminescence intensity. x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals retained more than 95% of their initial luminescence intensity.

Claims

1. A method for preparing blue luminescent core-shell structure nanocrystals, characterized in that It is carried out in the following steps: In an atmospheric environment, CsPbBr3 nanocrystals were mixed with CsCl and ground for 1 h to 4 h to obtain CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y nanocrystals, and then CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals are placed in a mixed solution of an organic solvent and a surfactant and allowed to stand, and finally centrifuged to obtain blue luminescent core-shell structure nanocrystals; The CsPbBr x Cl 3-x Where x>0, and 3-x>0; the Cs4PbBr y Cl 6-y In this case, y>0 and 6-y>0.

2. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The organic solvent is one of toluene, cyclohexane, dimethyl sulfoxide and acetone or a mixture of several of them.

3. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The surfactant is one of n-octanoic acid, n-octylamine, oleic acid and oleylamine or a mixture of several of them.

4. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The mass ratio of the CsPbBr3 nanocrystal to CsCl is 1:(0.2-4).

5. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The volume ratio of the organic solvent to the surfactant in the mixed solution of the organic solvent and the surfactant is 1:(0.001-0.1).

6. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The volume ratio of the mass of the nanocrystals to the mixed solution of the organic solvent and the surfactant is 1 mg: (0.1-10) mL.

7. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that In the atmosphere, CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals are placed in a mixed solution of an organic solvent and a surfactant and allowed to stand for 1 to 200 minutes.

8. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The centrifugation is specifically carried out at a rotation speed of 3000 rpm to 6000 rpm for 1 min to 10 min.

9. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that The grinding is mortar grinding or ball milling.

10. The method for preparing a blue luminescent core-shell structure nanocrystal according to claim 1, characterized in that CsPbBr3 nanocrystals were mixed and ground with CsCl for 2 h in an atmospheric environment to obtain CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y nanocrystals, and then in the atmosphere, CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The nanocrystals were placed in a mixed solution of an organic solvent and a surfactant and allowed to stand for 10 minutes, and finally centrifuged at a speed of 6000 rpm for 10 minutes to obtain blue luminescent core-shell structure nanocrystals; The organic solvent is toluene; The surfactant is a mixture of n-octanoic acid and n-octylamine; the volume ratio of n-octanoic acid to n-octylamine is 1:1; The mass ratio of the CsPbBr3 nanocrystals to CsCl is 1:0.8; The volume ratio of the organic solvent to the surfactant in the mixed solution of the organic solvent and the surfactant is 1:0.005; The CsPbBr x Cl 3-x / Cs4PbBr y Cl 6-y The ratio of the mass of the nanocrystals to the volume of the mixed solution of the organic solvent and the surfactant is 1 mg:0.1 mL.